Labor Migration and Social Development in Nepal - Aryal, Gokarna Raj (Journal of Population and Development, 2021)
This paper attempts to highlight the existing situation of labor migration and its impacts on social progress, and to analyze how migration and social development are interrelated in Nepal. In recent years, the number of overseas migrants has significantly increased in Nepal because of diversified roles of the migrants as employees, students, businesspersons and tourists. One sad aspect to these roles of the Nepalese foreign labor migrants abroad is that they leave their homeland country because of lack of job opportunity, poverty, insecurity, and lack of proper infrastructures, low salary and income, lack of market for agriculture produce and high cost of agriculture production. The paper has been prepared with the help of secondary data. Around 59, 55,051 labor migrants legally migrated to 136 different countries of the world in 2019 from Nepal. In Nepal, remittance occupies almost one-fourth of the total GDP of our country. However, the inflow of abroad migration has slightly decreased from fiscal year 2019 because of COVID-19 pandemic in Nepal, though the remittance inflow into Nepal is practically stable. However, the contribution of the inflow of remittance to the overall national development has been often debated. The remittance sent to Nepal by foreign migrants have played an vital role not only for earning foreign exchange but also for education, health, sanitation, poverty alleviation, production of goods and services, and social development. Labour migration and social development of Nepal are not only interrelated, but the one also influences the other in a positive way.